Pengembangan Framework Digital Forensics Investigation (FDFI) Pada Sosial Media Dengan Metode System Development Life Cycle (SDLC) - Nukman Nukman; Yudi Prayudi; Fetyata Yudha (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
From technological developments that are so increasingly competitive and increasingly needed in people's lives for their daily needs on social media as is often used by the community, namely Twitter, Facebook, Instagram, Youtube, WhatsApp and other social media. But the general public does not know that the data sent is stored on a central server so that other people can use the data to commit crimes such as taking identities so that it can be used as a tool to act to spread information that is not infallible for other crimes that can harm many people. Therefore, the researcher developed an investigative framework in social media as data collection using the System Development Life Cycle (SDLC) method. In developing this data collection framework, researchers used the Maltego tool as a means of proving the identity of the perpetrator. The designed framework will produce five stages, namely planning, analysis, design, maintenance, and implementation. The digital evidence that will be obtained from these tools includes twitter accounts, email addresses, phone numbers, DNS, websites and social media.